PHYSIOLOGICAL PROFILE IN NEONATE CALVES OF PURNATHADI BUFFALO - Kuralkar, Prajakta; Dhenge, SA; Nagre, SM; Kuralkar, SV (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was undertaken to record the variations in physiological parameters [body weight (BW), rectal temperature (RT), respiration rate (RR) and heart rate (HR)] in six Purnathadi buffalo calves. The parameters were recorded on day 0 (day of birth) and days 3, 10, 20 and 30 days of age. Rectal temperature and respiration rate was found to be non significant through out the 30 days study with overall mean of 100.93±0.14 oF and 22.33±0.64 breaths/min respectively. Heart rate was significantly high on the day of birth (106.47±2.48 beats/min) and dropped significantly with advancing age of 30 days (85.67±5.57 beats/min) with overall mean of 96.37±1.85 beats/min. Body weight was lower on day of birth (19.83±1.33 kg) and increased significantly as the age advances to 30 days (30.32±2.19 kg)